Choline chloride-zinc chloride deep eutectic solvent mediated preparation of partial O-acetylation of chitin nanocrystal in one step reaction. (15th September 2019) - Hong, Shu; Yuan, Yang; Yang, Qiuru; Chen, Ling; Deng, Junqian; Chen, Weimin; Lian, Hailan; Mota-Morales, Josué D.; Liimatainen, Henrikki
Highlights: One step hydrolysis and O -acetylation of chitin in deep eutectic solvent (DES). DES acted as non-volatile solvent and catalyst. Low concentration of acid is needed for the reaction. The obtained chitin is easy nanofibrillation and form nanocrystal with ultrasonication. Abstract: An efficient and one step production of acetylated and esterified chitin nanocrystals (CNCs) was successfully achieved using choline chloride-zinc chloride deep-eutectic solvent (ChCl-ZnCl2 DES). In this method, ChCl-ZnCl2 DES with a mole ratio of 1:2, was used for the esterification and O -acetylation of chitin at 90 °C for 3 h and 6 h. This strategy consisted in using ChCl-ZnCl2 DES as a green and non-volatile solvent for chitin under heterogeneous condition that, upon addition of acetic anhydride or acetic acid, simultaneous acetylation or esterification and hydrolysis occurred. The DES act as an efficient catalysis of the functional reaction. The acetylation and hydrolysis proceeded efficiently and the yield of partial acetylated CNCs was ca. 61.6% with DS (degree of substitution) of 0.23 under the optimized conditions. Acetic acid was used to substituted acid anhydride to produce CNCs. The yield of acetic acid induced CNCs was ca. 62.0% with higher DS of 0.34. A thorough investigation of the physicochemical characteristics changes of chitin pointed out that the main skeletal structure of obtained CNCs was intact. The thermal stability of CNCs decreased after treated by ChCl/ZnCl2 . In addition, thermal stability of CNCs functionalized with acetic acid is lower than the ones functionalized with acetic anhydride. DES showed low expenditure and toxicity. This approach provides a novel method for production of functional chitin nanocrystals.